The Role of the UPTD DP3AP2KB Depok City in Implementing Policies for Handling Cases of Sexual Violence and Abuse Against Children - Kurniawan, Yunan Prasetyo; Kesuma, Diani; Tarsono, Edy; Sekar Wangi, Tiara Ayu (Pancasila and Law Review, 2024)
Children are often vulnerable targets for adult aggression, resulting in various forms of violence including physical abuse, neglect, pornography, psychological abuse, and sexual violence. In Depok City, where such cases occur, the local government provides protection and assistance to child victims through the UPTD PPA DP3AP2KB. This research analyzes the factors hindering policy implementation, effective methods in addressing violence and sexual harassment against children, and the resulting impact on child protection under the UPTD PPA DP3AP2KB’s policies. Employing empirical research methods, data were collected through field interviews with resource persons from the UPTD DP3AP2KB of Depok City. Findings reveal that both internal and external factors hinder policy implementation. Additionally, six key service functions represent effective methods for assisting victims. The policy’s impact on child protection includes providing psychological support, addressing victims’ school-related challenges, and fulfilling families’ needs for legal proof. The research concludes that the UPTD PPA DP3AP2KB of Depok City implements its policies on handling violence and sexual abuse against children in accordance with existing regulations.